2021
DOI: 10.1212/nxi.0000000000000946
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Activation in Astrocytes by Laquinimod Ameliorates Autoimmune Inflammation in the CNS

Abstract: ObjectiveMS is an autoimmune demyelinating disease of the CNS, which causes neurologic deficits in young adults and leads to progressive disability. The aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor, can drive anti-inflammatory functions in peripheral immune cells and also in CNS-resident cells. Laquinimod is a drug developed for the treatment of MS known to activate AHR, but the cellular targets of laquinimod are still not completely known. In this work, we analyzed the contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…This was further recapitulated in the recent CONCERTO trial, in which oral Laq treatment led to a significant reduction in brain volume loss compared to the placebo group, as well as a numerical reduction in time to first relapse and annualized relapse rate as exploratory endpoints, while it did not alter 3-month confirmed disability progression ( 43 ). Together with observations of protective astrocyte signaling following oral administration of Laq during EAE ( 28 ), one may speculate that this positive effect of Laq on GM loss may, at least to some extent, be carried by increased levels of PTN, which limits inflammatory signaling in glial cells and supports neuronal survival, as we have demonstrated in vitro and in vivo . However, a detailed examination of brain tissue obtained from Laq-treated MS patients would be needed to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 75%
“…This was further recapitulated in the recent CONCERTO trial, in which oral Laq treatment led to a significant reduction in brain volume loss compared to the placebo group, as well as a numerical reduction in time to first relapse and annualized relapse rate as exploratory endpoints, while it did not alter 3-month confirmed disability progression ( 43 ). Together with observations of protective astrocyte signaling following oral administration of Laq during EAE ( 28 ), one may speculate that this positive effect of Laq on GM loss may, at least to some extent, be carried by increased levels of PTN, which limits inflammatory signaling in glial cells and supports neuronal survival, as we have demonstrated in vitro and in vivo . However, a detailed examination of brain tissue obtained from Laq-treated MS patients would be needed to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 75%
“…A long list of synthetic [1,[7][8][9][10][11][12][13], endogenous [14,15] and dietary molecules [16] have been identified that bind to AhR, in addition to ligands produced by commensal microbiota [17]. There is significant interest in developing AhR-targeted therapeutics for multiple diseases, particularly autoimmune disorders [18][19][20] and cancer [3,[8][9][10]21,22]. The feasibility of therapeutically targeting AhR is supported by the absence of overt toxicity in vivo when select highaffinity ligands are administered [11,19,20].…”
mentioning
confidence: 99%
“…Treatment of human astrocytes with LQ inhibited IL-1β-induced downregulation of glutamate transporters GLAST and GLT1 and restored astrocyte glutamate uptake ( 178 ). Consistently, LQ treatment ameliorated EAE by suppressing, in astrocytes, the expression of inflammatory mediators such as IL-6 and ROS and by inducing a transcriptional program associated to homeostatic chemokines, neurotrophin, axonal guidance and transendothelial migration ( 182 ).…”
Section: Dysregulation Of Astrocyte Functions By Inflammatory T Cells...mentioning
confidence: 93%